Determinants of Variables That Affect Electrical Energy Consumption in Indonesia 2011-2020 - Akbar, Leon; Mafruhah, Izza; Gravitiani, Evi (International Journal of Energy Economics and Policy, 2024)
This study aims to analyze the determinants of variables that affect electricity consumption in Indonesia 2011-2020. There are 4 variables that are used as determinant variables, namely (1) economic growth, (2) population growth, (3) Human Development Index (HDI), and (4) internet access. This study uses a random effect model regression method using data that is panel data consisting of 34 provinces in Indonesia in the span of 2011 - 2020. Secondary data were obtained from the Central Statistics Agency (BPS), a statistical report of PT. PLN (Persero) and previous research literature studies. The results of this study found that (1) the variable of economic growth did not affect electricity consumption, (2) the population growth variable also did not affect the consumption of electricity, (3) the variable Human Development Index (HDI) had a positive effect on electricity consumption and (4) internet access variable has a negative effect on electricity consumption. Suggestions that the author can convey are: (1) optimizing the potential of New Renewable Energy (EBT), (2) conserving electricity and making efficient use of electricity, (3) increasing the electrification ratio so that electricity can be enjoyed by the entire community.